Accounting and financial reporting of economic entities: adaptation of Ukrainian legislation to the standards of the European Union. Issue 1 (2nd January 2020) - Bodnar, Tatyana V.; Reznikova, Viktoria V.; Patsuriia, Nino B.; Radzyviliuk, Valeria V.; Kravets, Iryna M.
Abstract : The article is devoted to today's most pressing issues of adaptation of the Ukrainian legislation on accounting and financial reporting of economic entities to the standards of the European Union. The paper defines the concepts of accounting, accounting statements, financial reporting, accounting organization, establishes the key task of accounting, the purpose of financial reporting. The article provides grounds for the conclusion that the economic relations regarding organization and management of accounting in Ukraine, compilation, presentation and disclosure of financial statements by economic entities are regulated by a multilevel system of normative legal acts with different legal effects. The paper has analyzed the novelties of the accounting legislation and provided suggestions for further improvement of legislation on accounting and financial reporting regulation. The article has explored the status and outlined the prospects for further adaptation of the provisions of normative legal acts, which regulate procedures of accounting management and financial reporting.